Programmable metamaterials with digital synthetic impedance circuits for vibration control - Yi, Kaijun; Matten, Gaël; Ouisse, Morvan; Sadoulet-Reboul, Emeline; Collet, Manuel; Chevallier, Gaël (Smart materials and structures, 2020)
This paper studies a new type of smart metamaterial consisting of piezoelectric actuators and digital synthetic impedance circuits (digital circuits). The digital circuit contains a micro-controller. By programming the micro-controller, the circuit can establish any desired impedance between the terminals of the connected piezoelectric patch, therefore to program the dynamical behaviors of the designed metamaterial. In this sense, a programmable metamaterial is studied. Experiments are conducted to study its programmable dynamical behaviors, with a particular focus on vibration reduction. Numerical simulations are also done in this work to qualitatively verify the experimental results. Different design methods are used to customize the dynamical behaviors of the designed metamaterial. Results demonstrate that the proposed smart metamaterial can be flexibly programmed online to reduce vibration at desired frequencies or within a large frequency band. The proposed programmable metamaterial conception can be naturally extended to other kinds of structures like plates and shells, they are promising components in the future adaptive structures.